LEARNING PSYCHOLOGY COURSE CONTRIBUTION IN PREPARING PROSPECTIVE PROFESSIONAL TEACHERS OF ISLAMIC RELIGIOUS EDUCATION - Wirdayanti Arsan; Sabarudin; Sjakir Lobud; Askar; Arifuddin M. Arif (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2023)
Abstrak This qualitative research with a phenomenological approach aims to analyze the role of the PAI learning psychology course in preparing professional teacher candidates for students majoring in PAI, Faculty of Tarbiyah and Teacher Training UIN Datokarama Palu, and to describe the lecture strategies used by lecturers for this purpose. Data collection was carried out through in-depth interviews, involved observation, and documentation. To ensure the validity of the data used triangulation of sources and techniques. Data analysis was carried out qualitatively through data collection, reduction, presentation, and analysis stages. The results of the study show that several roles in the PAI learning psychology course play a role in preparing professional teacher candidates, such as: providing awareness of the different characteristics of students, providing a broad understanding of the duties and roles of teachers, and giving students self-confidence. pursue the profession of a teacher. The strategy used in PAI Learning Psychology lectures is to combine interactive lecture methods, discussions, use of infocus media and digital media through video analysis, and presentation of material with PowerPoint. In addition, problem-based learning is also the most frequently used strategy. With this strategy, students not only receive material but are invited intensively to solve problems related to psychological problems in learning.